1997
DOI: 10.1073/pnas.94.11.5568
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the thyroid Na + /I symporter with an anti-COOH terminus antibody

Abstract: The Na ؉ ͞I ؊ symporter (NIS) is the plasma membrane protein that catalyzes active I ؊ transport in the thyroid, the first step in thyroid hormone biogenesis. The cDNA encoding NIS was recently cloned in our laboratory and a secondary structure model proposed, suggesting that NIS is an intrinsic membrane protein (618 amino acids; Ϸ65.2 kDa predicted molecular mass) with 12 putative transmembrane domains. Here we report the generation of a site-directed polyclonal anti-COOH terminus NIS antibody (Ab) that immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
142
0
8

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 209 publications
(166 citation statements)
references
References 16 publications
13
142
0
8
Order By: Relevance
“…NIS expression was not detected in cells overexpressing RasS35 by 30-fold. The broad band detected with the NIS antibody in WRT cells is virtually identical to that reported in FRTL-5 cells (Levy et al, 1997). Similar results were obtained in four experiments using RasC40 B3 cells, two experiments with RasC40 P6 cells, and in three experiments in RasS35 cells cells, TSH retains the ability to induce the expression of thyroid-speci®c genes in RasC40 cells.…”
Section: Expression Of Rasc40 Is Compatible With Thyroid Differentiationsupporting
confidence: 84%
“…NIS expression was not detected in cells overexpressing RasS35 by 30-fold. The broad band detected with the NIS antibody in WRT cells is virtually identical to that reported in FRTL-5 cells (Levy et al, 1997). Similar results were obtained in four experiments using RasC40 B3 cells, two experiments with RasC40 P6 cells, and in three experiments in RasS35 cells cells, TSH retains the ability to induce the expression of thyroid-speci®c genes in RasC40 cells.…”
Section: Expression Of Rasc40 Is Compatible With Thyroid Differentiationsupporting
confidence: 84%
“…Experimental testing has confirmed this topology and revealed that the N terminus faces the extracellular milieu and the long C terminus the cytosol (14). NIS is glycosylated at three positions-N225, N489, and N502 (15) (Fig.…”
mentioning
confidence: 87%
“…SDS/PAGE, electrotransference to PVDF membranes, and immunoblotting were carried out as previously described (14). Membranes were incubated with 4 nM of an affinity-purified polyclonal anti-rat NIS Ab directed against 16 residues of the cytosolic NIS carboxyl terminus.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of thyroid membrane fractions by N-glycosidase F in the presence of SDS led to the transformation of the 75-to 80-kd hNIS protein into a main component of ϳ50 kd, likely representing the nonglycosylated (nG) hNIS polypeptide chain as found for rat NIS. 18,19 In the absence of SDS, the enzyme had a lower efficiency and generated two main intermediate forms and a low amount of the 50-kd species. The hNIS deglycosylation pattern ( Figure 6) composed of two partially glycosylated forms named pG1, pG2, and nG was reproducibly obtained.…”
Section: Hypofunctioning Benign and Malignant Tumors Only Express Lowmentioning
confidence: 99%